Intonation of Russian Declarative Sentence: Methodology for Teaching Foreign Students - Shutova, Marina Nikolaevna (2020)
The article deals with teaching Russian intonation of declarative sentences to foreign students. The emphasis is placed on the way teaching materials are presented. In particular, the variable rows for intonation patterns in declarative sentences have been developed, as well as the teaching of syntagmatic segmentation and intonation patterns in complex utterances. This method of working with foreigners is efficient for teaching foreign students the Russian declarative intonation which manifests in verbal communication and reading.